Periodontal Diseases in Diabetics Who Use Betel Nuts and Smoke in Bangladesh (Journal of Dentistry and Allied Science, 2025)
The Diabetic Clinic in Rajshahi and the Department of Preventive and Children Dentistry at Bangabandhu Sheikh Mujib Medical University (BSMMU) in Dhaka conducted a cross-sectional study from April to December 2023. Examining the role of chewing tobacco, betel nut, or both in the development of a higher periodontal index was the goal of the study. Between the ages of 19 and 79, 34 men and 47 women made up the study population. A semi-structured questionnaire was used for interviews and oral examinations to collect the data. The statistical analysis was conducted using SPSS 16.0. According to the study’s findings, every participant brushed their teeth on a frequent basis. Among the targeted diabetic individuals, the study revealed an intriguing correlation between tobacco use and chewing betel nut and periodontitis. It is believed that tobacco and betel nut users may benefit diabetics’ periodontal health in light of the study’s link. Nevertheless, more research is advised to ascertain the effects of tobacco and betel nut in lowering blood sugar and, consequently, periodontitis in diabetics.  Journal of Dentistry and Allied Science, Vol. 8 No 2: 67-76